Antibiotic treatment induces long-lasting changes in the fecal microbiota that protect against colitis - Ward, Naomi L. (Inflamm Bowel Dis, 2016)
BACKGROUND: The interplay between host genetics, immunity, and microbiota is central to the pathogenesis of inflammatory bowel disease (IBD). Previous population-based studies suggested a link between antibiotic use and increased IBD risk, but the mechanisms are unknown. The purpose of this study was to determine the long-term effects of antibiotic administration on microbiota composition, innate immunity, and susceptibility to colitis, as well as the mechanism by which antibiotics alter host colitogenicity. METHODS: Wild-type mice were given broad-spectrum antibiotics or no antibiotics for two weeks, and subsequent immunophenotyping and 16S rRNA gene sequencing-based analysis of the fecal microbiome were performed six weeks later. In a separate experiment, control and antibiotic-treated mice were given seven days of DSS, six weeks after completing antibiotic treatment, and the severity of colitis scored histologically. Fecal transfer was performed from control or antibiotic-treated mice to recipient mice whose endogenous microbiota had been cleared with antibiotics, and the susceptibility of the recipients to DSS-induced colitis was analyzed. Naïve CD4+ T cells were transferred from control and antibiotic-treated mice to immunodeficient Rag-1-/- recipients and the severity of colitis compared. RESULTS: Antibiotics led to sustained dysbiosis and changes in T-cell subpopulations, including reductions in colonic lamina propria total T cells and CD4+ T cells. Antibiotics conferred protection against DSS colitis, and this effect was transferable by fecal transplant but not by naïve T cells. CONCLUSIONS: Antibiotic exposure protects against colitis, and this effect is transferable with fecal microbiota from antibiotic-treated mice, supporting a protective effect of the microbial community.